The Use of Personalized Medicine in Pancreatic Ductal Adenocarcinoma (PDAC): New Therapeutic Opportunities - Inês Mendes; Nuno Vale (Future Pharmacology)
Pancreatic cancer constitutes a significant cause of cancer-related fatalities, with a five-year survival rate of only 12%. The most prevalent form of this disease is pancreatic ductal adenocarcinoma (PDAC). Given that a single therapeutic intervention has proven inadequate for the treatment of PDAC, it is essential to identify distinct molecular signatures that could improve treatment efficacy and alleviate the economic burden on patients. Surgery is recognized as the most effective treatment option for PDAC; however, only a small percentage of patients are candidates for this procedure due to the advanced stage of the disease at the time of diagnosis. In this context, we propose to explore the biology of PDAC with a focus on microbiome, epigenetics, and genetics. Our objective is to examine the existing knowledge in these areas and to identify potential pathways for personalized medicine. This approach holds promise for advancing our understanding of PDAC development, progression, and resistance to standard therapy.